Assessing the Financial Sustainability of Jamaica's HIV Program - World Bank (World Bank, Washington, DC, 2017)
Jamaica has made many notable achievements in the fight against HIV/AIDS, which include a robust treatment program and improved HIV prevention programs that increasingly focus on the key drivers of the HIV epidemic and which are based on evidence. These attainments have resulted in a sustained decline in the estimated incidence of HIV and in a reduction in AIDS mortality. The national response to HIV/AIDS in Jamaica is currently financed by the Government as well as by several external sources, including the World Bank, the Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund) and the United States government. It is expected, however, that external financing will cease or be significantly reduced in the next two years. As a result, a substantial increase in domestic financing for the national HIV/AIDS response will be needed. However, public debt levels are high, and the country is feeling the repercussions of the global financial crisis, thus the availability of domestic resources is and will be very tight. Any shortfall in financing whether domestic, external or both will have serious implications for the delivery of HIV services. The Government of Jamaica requested this study so as to inform its future HIV/AIDS policy response. This study is one input in a series of actions that the Government will undertake to formulate a future sustainability plan and investment framework for the National HIV Program. This study was led and financed by the World Bank and conducted in collaboration with the Government of Jamaica and United Nations Programme on HIV/AIDS (UNAIDS). The study aimed to assess the sustainability of Jamaica's National HIV Program from a fiscal perspective. Specifically, the purpose of the study was to: 1) review current spending on HIV/AIDS and the sources of financing; 2) estimate the fiscal burden of the national HIV/AIDS response and assess the outlook for external financing of the HIV program; 3) project how the epidemic will unfold as well as what the costs would be under different potential scenarios; and 4) provide recommendations to inform policy decisions.